(untitled) (Publicacions de la Universitat de València, 2023)
This book aims to bring together the new advances and knowledge the fields where optometrists research and contribute their professional services to society. The chapters describe research results obtained by final year students of the Degree in Optics and Optometry, Master’s Degree in Advanced Optometry and Vision Sciences, Doctorate, and also by recent graduates, often under the direction of a senior researcher. Some of them have been carried out in the university environment and others in hospitals or medical centres, with the support and collaboration of the ophthalmologists and optometrists in the staff. All this shows the interest of optometrist in scientific research and the importance of interdisciplinary collaboration, with the common goal of improving the visual health of society. Para mejorar la salud visual de la población y, en concreto, la atención a los usuarios de los servicios de Óptica y Optometría es fundamental integrar los estudios más avanzados en la práctica diaria de los profesionales y fomentar la colaboración multidisciplinar en la investigación. Con el fin de contribuir a este objetivo, se reúnen un conjunto de textos que difunden nuevos conocimientos en este ámbito sanitario. Las investigaciones han sido desarrolladas por estudiantes de último curso del Grado en Óptica y Optometría, del Máster en Optometría Avanzada y Ciencias de la Visión y de doctorado, pero también por titulados recientes, a menudo bajo la dirección de investigadores senior. Algunas de ellas han sido realizadas en el ámbito universitario y otras en hospitales o centros médicos, con el apoyo y la colaboración de oftalmólogos y optometristas que trabajan en estos, para potenciar las sinergias y ampliar la red de la comunidad científica.